2009
DOI: 10.1007/s11270-008-9973-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Contaminants on the Genome of Some Species of Genus Chironomus (Chironomidae, Diptera) Live in Sediments of Dunajec River and Czorsztyn Reservoir

Abstract: The effect of contaminants on the genomes of Chironomus plumosus L. and Chironomus bernensis Wülker, Klötzli species was studied in the Dunajec River (station 1) and in the littoral of Czorsztyn Reservoir (stations 2 and 3). According to the index of geoaccumulation, the sediments were polluted by cadmium (Cd) and chromium (Cr). Cd concentrations at stations 1, 2, and 3 were 0.71, 0.56, and 1.27 μg g −1 , while Cr concentrations were 841.5, 186.9, and 40.7 μg g −1 , respectively. The pH of sediments ranged fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…The level of NOR activity decreased to the intermediate level in 43% of the cells. The centromere regions were in a heterozygous depressed state in 50% of the larvae collected from the two trace-metal-polluted Polish stations (Michailova et al 2009c), while this phenomenon was not observed in larvae from the Bulgarian station (Ilkova 2004). In the industrialand urban-waste-contaminated Finnish stations, no somatic aberrations were found (S index = 0).…”
Section: Genus Chironomus Meigenmentioning
confidence: 90%
See 4 more Smart Citations
“…The level of NOR activity decreased to the intermediate level in 43% of the cells. The centromere regions were in a heterozygous depressed state in 50% of the larvae collected from the two trace-metal-polluted Polish stations (Michailova et al 2009c), while this phenomenon was not observed in larvae from the Bulgarian station (Ilkova 2004). In the industrialand urban-waste-contaminated Finnish stations, no somatic aberrations were found (S index = 0).…”
Section: Genus Chironomus Meigenmentioning
confidence: 90%
“…The S indexes were 0.10 in the Bulgarian station (estimated from data in Ilkova 2004). The S indexes were 0.5 and 0.8 in the two Polish stations (estimated from data in Michailova et al 2009c). The levels of activity of BR 2 /BR 3 were analyzed only in the Bulgarian station, where in ∼80% of the cells both BRs significantly decreased their activity levels to levels of complete depression (Ilkova 2004).…”
Section: Genus Chironomus Meigenmentioning
confidence: 96%
See 3 more Smart Citations